Barriers and facilitators to the participation and engagement of primary care in shared-care arrangements with community mental health services for preventive care of people with serious mental illness: a scoping review - Sharon M. Parker; Katrina Paine; Catherine Spooner; Mark Harris (BMC, 2023)
Abstract Background People with serious mental illness die about 20 years earlier than the general population from preventable diseases. Shared-care arrangements between general practitioners and mental health services can improve consumers' access to preventive care, but implementing shared care is challenging. This scoping review sought to describe current evidence on the barriers and facilitators to the participation and engagement of primary care (specifically general practitioners) in shared-care arrangements with community mental health services for preventive health care of this population. Methods We searched Medline, Embase, CINAHL, Scopus, APA PsychINFO and EBM Reviews from 2010 to 2022. Data was extracted against a Microsoft Excel template developed for the review. Data was synthesised through tabulation and narrative methods. Results We identified 295 records. After eligibility screening and full-text review, seven studies were included. Facilitators of engagement included a good fit with organisation and practice and opportunities to increase collaboration, specific roles to promote communication and coordination and help patients to navigate appointments, multidisciplinary teams and teamwork, and access to shared medical/health records. Barriers included a lack of willingness and motivation on the part of providers and low levels of confidence with tasks, lack of physical structures to produce capacity, poor alignment of funding/incentives, inability to share patient information and challenges engaging people with severe mental illness in the service and with their care. Conclusion Our results were consistent with other research on shared care and suggests that the broader literature is likely to be applicable to the context of general practitioner/mental health services shared care. Specific challenges relating to this cohort present difficulties for recruitment and retention in shared care programs. Sharing "goals and knowledge, mutual respect" and engaging in "frequent, timely, accurate, problem-solving communication", supported by structures such as shared information systems are likely to engage primary care in shared care arrangements more than the traditional focus on incentives, education, and guidelines.